PARAMETRIC MODELING AS AN INNOVATIVE APPROACH IN GRAPHIC DESIGN - LIU , W.; KOLISNYK , O. (Art and Design, 2024)
Purpose. The article focuses on exploring the possibilities and strategies of innovative integration of parametricism into the field of graphic design and analyzing the main problems and potential solutions in using parametric design in creating graphic objects. Methodology. According to the research topic, the methods employed include comparative study, theoretical analysis, and synthesis. Results. The article discusses the definitions and characteristics of parametric design, examines its applications for optimizing design thinking and creating personalized objects. Various levels of innovative implementations are presented, offering several strategies for integrating parametric modeling into graphic design, including visual element generation, layout optimization, design interactivity enhancement, and data visualization in personalized design. Additionally, integration challenges related to the use of artificial intelligence technologies are discussed. Scientific novelty. The article analyzes various levels and effective strategies for applying parametric modeling in the field of graphic design, exploring current aspects of interaction that are innovative and emphasizing the importance of utilizing parametric design methodology, artificial intelligence, and computational design in the paradigm of contemporary graphic design. Practical significance. The materials presented in the article can be utilized for investigating the innovative application of digital design, parametric design, and artificial intelligence in the field of graphic design.